HUBUNGAN USIA DAN PEKERJAAN IBU DENGAN KURANG ENERGI KRONIK PADA IBU HAMIL - Saputri, Ringga Fardhani; Astuti, Dwi Woro; Saleh, Asep Jalaludin (JURNAL WACANA KESEHATAN, 2025)
Chronic energy deficiency (CED) during pregnancy is still a serious problem because it can impact the health and safety of mothers and babies as well as the quality of babies born. The factor that causes pregnant women to experience CED is due to lack of nutritional consumption. However, increasing the incidence of CED in pregnancy can also be influenced by various factors, including occupational factors and maternal age at pregnancy. The purpose of this study is to determine the correlation of between age and profession of mothers with chronic energy deficiency in pregnant women in the Donomulyo Lampung Community Health Center. The research design used an analytic study with a cross sectional design, the population in this study were pregnant women in the working area of the Donomulyo Public Health Center, East Lampung, totaling 191 people. The sample used was 130 people. The analysis in this study used the Chi square test. The results of statistical tests show that the distribution of the incidence of CED in pregnant women is found to be 10.8%, most of the pregnant women are between the ages of 20-35 years (64.6%), and the employment is not working (56.9%). The results of the analysis of the age variable obtained p-value = 0.034; OR: 3,843; and job variable p-value = 0.044; OR: 5,304. It is concluded that there is a mother's age and occupation with the incidence of CED in pregnant women